Design of electrically driven single photon source based on dielectric passive cavity structure at 1.3 μm. (December 2020) - Blokhin, S A; Bobrov, M A; Maleev, N A; Blokhin, A A; Vasyl'ev, A P; Kuzmenkov, A G; Shchukin, V A; Ledentsov, N N; Reitzenstein, S; Ustinov, V M
Abstract: A combination of advanced concepts is applied for designing micro-cavity structures aimed for single-photon sources with high photon-extraction efficiency in the telecom O-band at 1.3 μm. The device design consists of a broad stop-band bottom distributed Bragg reflector (DBR), a top DBR formed in a dielectric micropillar with additional circular Bragg grating and a central dielectric passive cavity. This combination of photonic elements is compatible with electric carrier injection and provides overall photon-extraction efficiency of 83% as shown by 3D finite-difference time-domain simulations.